2007
DOI: 10.1007/s11094-008-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activity of total bufadienolides from the Central-Asian Bufo viridis toad venom

Abstract: The chemical composition of bufadienolides isolated from the venom of Bufo viridis green toad occurring in Central Asia was determined and their biological properties were studied. Six individual bufadienolides were isolated by reverse-phase chromatography on a Lichrosorb RP-8 (10 m) column in amounts sufficient for qualitative analysis. Two of these were previously identified as arenobufagin and gamabufotalin by NMR spectroscopy and x-ray diffraction methods. The chemical structures of four other bufadienolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…An overview of well-known bufadienolide-containing Bufo species was included in a comprehensive review. 2 Recent investigations indicated that bufadienolides are present in several diverse anurans [56][57][58][59][60] of the Bufonidae family, except Melanophryniscus species. 61,62 A hemisuberate of hellebrigenin 52 was isolated from the skin of Bufo bufo gargarizans, 63 and three unusual bufadienolide conjugates, 11a,19-dihydroxytelocinobufagin-3-(12-hydroxydodecanoic acid ester) 53, 11a,19-dihydroxytelocinobufagin-3-(14-hydroxy-7-tetradecenoic acid ester) 54 and 11a, 19-dihydroxytelocinobufagin-3-(14-hydroxytetradecanoic acid ester) 55, were separated from the ovaries of the cane toad, B. marinus.…”
Section: Bufonidaementioning
confidence: 99%
“…An overview of well-known bufadienolide-containing Bufo species was included in a comprehensive review. 2 Recent investigations indicated that bufadienolides are present in several diverse anurans [56][57][58][59][60] of the Bufonidae family, except Melanophryniscus species. 61,62 A hemisuberate of hellebrigenin 52 was isolated from the skin of Bufo bufo gargarizans, 63 and three unusual bufadienolide conjugates, 11a,19-dihydroxytelocinobufagin-3-(12-hydroxydodecanoic acid ester) 53, 11a,19-dihydroxytelocinobufagin-3-(14-hydroxy-7-tetradecenoic acid ester) 54 and 11a, 19-dihydroxytelocinobufagin-3-(14-hydroxytetradecanoic acid ester) 55, were separated from the ovaries of the cane toad, B. marinus.…”
Section: Bufonidaementioning
confidence: 99%
“…Our early trials enabled us to isolate the sum of bufadienolides from Bufo viridis toad venom, that contained arenobufagin, gamabufotalin, telocinobufagin, marinobufagin, bufarenogin, and bufalin [19]. We further established that the sum of bufadienolides at 0.046-0.093 mg/kg concentration did not reveal embryotoxic and teratogenic effects in rats [20].…”
Section: Introductionmentioning
confidence: 81%
“…A 20 μg/mL dose of extract was found to enhance Ca 2+ in cardiomyocytes (Soliev et al, 2007). Previously, the ionotropic effect of the sum of bufadienolides was associated with the inhibition of Na + /K + -ATPase and partially with Ca 2+ -ATPase of the endoplasmic reticulum (Usanova et al, 2002).…”
Section: Effects Of Bufadienolides On Atpase Activitymentioning
confidence: 95%
“…The effects of the purified sum on the content of mitochondrial calcium were established, and based on it, we developed drug composition called Bakagin. A 20 μg/mL dose of extract was found to enhance Ca 2+ in cardiomyocytes (Soliev et al, 2007). Previously, the ionotropic effect of the sum of bufadienolides was associated with the inhibition of Na + /K + ‐ATPase and partially with Ca 2+ ‐ATPase of the endoplasmic reticulum (Usanova et al, 2002).…”
Section: Effects Of Bufadienolides On Atpase Activitymentioning
confidence: 99%